Neural mechanisms of expert persuasion on willingness to pay for sugar - Ntoumanis, Ioannis; Davydova, Alina; Sheronova, Julia; Panidi, Ksenia; Kosonogov, Vladimir; Shestakova, Anna N.; Jääskeläinen, Iiro P.; Klucharev, Vasily (Frontiers in Behavioral Neuroscience, 2023)
Sugar consumption is associated with many negative health consequences. It is, therefore, important to understand what can effectively influence individuals to consume less sugar. We recently showed that a healthy eating call by a health expert can significantly decrease the willingness to pay (WTP) for sugar-containing food. Here, we investigate which aspects of neural responses to the same healthy eating call can predict the efficacy of expert persuasion. Forty-five healthy participants performed two blocks of a bidding task, in which they had to bid on sugar-containing, sugar-free and non-edible products, while their electroencephalography (EEG) was recorded. In-between the two blocks, they listened to a healthy eating call by a nutritionist emphasizing the risks of sugar consumption. We found that after listening to the healthy eating call, participants significantly decreased their WTP for sugar-containing products. Moreover, higher intersubject correlation of EEG (a measure of engagement) during listening to the healthy eating call resulted in a larger decrease in WTP for sugar-containing food. Whether or not a participants’ valuation of a product was highly influenced by the healthy eating call could also be predicted by spatiotemporal patterns of EEG responses to the healthy eating call, using a machine learning classification model. Finally, the healthy eating call increased the amplitude of the P300 component of the visual event-related potential in response to sugar-containing food. Overall, our results shed light on the neural basis of expert persuasion and demonstrate that EEG is a powerful tool to design and assess health-related advertisements before they are released to the public.